Inclusion of People with Disability in the Church Community Life in the Perspective of Disabled Individuals - Zielińska-Król, Katarzyna; Szot, Leon (Verbum Vitae, 2024)
The physical presence of people with disability in the extent of the parish community is based on two main components: (I) activities undertaken by a priest to organize religious life, including those for people with disability, and (II) activities undertaken by people with disability within the parish community. The aim of the article is to answer the question: What is the importance of a priest in the context of the presence of people with disability in the church community? The empirical article is based on results of the nationwide qualitative research that was conducted among people with disabilities (using the FGI group interview; targeted group selection; the participants of the study were people with physical disabilities, deaf and hearing impaired, blind and visually impaired, and people with intellectual disabilities). The analysis of the data obtained allows us to put forward the thesis that the inclusion of people with disability in parish life is a consequence of a close, personal relationship with a priest who has at least basic knowledge of the physical, mental, and sometimes also intellectual capabilities of a faithful person with disability. The results obtained may constitute a contribution to pastoral discernment regarding the factors influencing the presence of people with disability in the Church community.